Brachiopods of the Itararé Group from Mafra county, southern Brazil, and their geological significance - Neves, Jacqueline. P. (2017)
Two remarkable brachiopod-bearing occurrences are recorded in the Late Paleozoic deposits of the Paraná Basin, cropping-out in the Mafra county, State of Santa Catarina, southern Brazil. These deposits belong to the upper-mid part of Itararé Group, known as Mafra and Lontras assemblages. The first one belong to the mid portion of the Mafra Formation, recorded in the Potreiro Farm outcrop. The second brachiopod occurrence is recorded in a 1.5-m-thick deposit of dark siliceous shales (Lontras shale), in which fossil remains are extremely abundant. Shells come from the Campáleo outcrop, located close to the BR-280 highway, 2km far from Mafra county. These shales are referred to the upper part of the Campo Mourão Formation. Until now, only two species of brachiopods were formally described or identified for these assemblages (i.e., Lingula imbituvensis Oliveira, Orbiculoidea guaraunensis Oliveira). Hence, the brachiopods faunas above are here described and/or revised, based on the available material deposited in the CENPALEO scientific collection (Contestado University). Preliminary results of our systematic survey indicated that both faunas are much diverse than previously realized. The Lontras shale brachiopod assemblage includes: Biconvexiella roxoi (Oliveira), Quinquenella? sp., Beecheria? sp., Langella imbituvensis (Oliveira), and Orbiculoidea guaraunensis Oliveira. On the other hand, the Mafra assemblage is composed by B. roxoi, Q. rionegrensis?, L. imbituvensis, and O. guaraunensis. Therefore, both assemblages show various taxa in common. It is noteworthy that the species L. imbituvensis, B. roxoi and Q. rionegrensis are also recorded in the upper part of the Taciba Formation, in Teixeira Soares region, State of Paraná. This is significant since: a- suggests a close faunal affinity among those brachiopodassemblages from distinct units of the Itararé Group; b- indicates that the stratigraphic range of those three above mentioned species is very wide, in which the oldest occurrence is recorded in the mid portion of the Mafra Formation and the youngest one in the uppermost portion of the Taciba Formation. Finally, both faunas are remarkable since they precede the record of the Eurydesma fauna, which thrived in the Paraná Basin, during the deposition of the Taciba Formation.